Time to first and sustained improvement in WOMAC domains among patients with osteoarthritis receiving tanezumab. Issue 3 (September 2022) - Hunter, D.J.; Schnitzer, T.J.; Hall, J.; Semel, D.; Davignon, I.; Cappelleri, J.C.; Bushmakin, A.G.; Abraham, L.
Abstract: Objective: To assess onset of effect in three placebo- or nonsteroidal anti-inflammatory drug (NSAID)-controlled trials of tanezumab in patients with moderate-to-severe osteoarthritis. Methods: Post-hoc nonparametric Kaplan–Meier analyses were used to estimate median time to first improvement and to sustained improvement in Western Ontario and McMaster Universities Osteoarthritis Index domain (Pain, Physical Function, Stiffness) scores across a range of improvement thresholds (0–100%, in 5% increments). Time to first improvement was defined as the first week scores met the pre-specified threshold. Time to sustained improvement was defined as the first week scores met the pre-specified threshold and were sustained (on average) for the remainder of the treatment period. Results: Across all domains, tanezumab-treated patients had shorter median times to first improvement (at most thresholds) and reached higher levels of improvement than placebo-treated patients. No substantial differences were observed between tanezumab doses (2.5 and 5 ​mg), or between tanezumab and NSAIDs. Most patients experiencing an event of first improvement went on to experience a sustained event. At low thresholds, sustained improvement occurred simultaneously with, or shortly after, first improvement. At higher thresholds, median time to sustained improvement was longer than median time to first improvement. Conclusions: Following initiation of tanezumab treatment, first improvement of osteoarthritis symptoms of 30% was evident within 2–4 weeks and sustained improvement was evident within 2–8 weeks. Time to improvement of 50% was more variable, with first and sustained events expected within 4–16 and 8–24 weeks, respectively. ClinicalTrials.gov identifiers: NCT02697773; NCT02709486; NCT02528188.